Fly like a Bird. - Colozza, A. (IEEE spectrum)
This paper discusses the development of a new aircraft based on a bird's flying principle. As currently envisioned, the ultra-slim vehicle would be unmanned, solar-powered, and made of strong, lightweight materials. Rather than a metal framework covered by riveted plates and hydraulically actuated parts, the plane's body and wings would consist of a plastic-like material called an ionic polymer-metal composite, which deforms when exposed to an electric field. If the voltages are applied just right, the material can be made to flap like a wing. On top of the composite wings would be paper-thin sheets of photovoltaic material and lithium-ion batteries, layered on by thin-film deposition. Energy efficiency is the largest benefit in this project. The solid-state aircraft would have many potential uses; gathering scientific data, relaying communications, and surveying terrain are but a few.